Iron ore tailings as a source of nutrients to the coastal zone. (October 2021) - Costa, Eduardo Schettini; Cagnin, Renata Caiado; da Silva, Cesar Alexandro; Longhini, Cybelle Menolli; Sá, Fabian; Lima, Ana Teresa; Gomes, Luiz Eduardo de Oliveira; Bernardino, Angelo Fraga; Neto, Renato Rodrigues
Abstract: The Fundão dam rupture was one of the largest environmental disasters worldwide and released millions of m 3 of iron ore tailings into the Doce River basin in southeastern Brazil. Here we assessed the supply of dissolved nutrients associated to tailings in the Doce River estuary and its adjacent coastal zone. First, we observed an acute increase in dissolved silicates (From 16.26 μM to 175.47 μM) and nitrate (From 5.56 μM to 50.69 μM) in the estuary when compared to days prior to the event. Coastal marine ecosystems showed significant concentrations of nitrite (From 0.72 μM to 2.99 μM) and phosphate (From 0.09 μM to 2.30 μM) one year after the disaster, which we attribute mainly to nutrient recycling. The chronic effects include an increase in nutrient load to the coastal zone with a predominance of nitrogenous species, which may increase the limitation of phosphorus and silica to marine primary production. Highlights: Mining tailing drastically changes nutrients concentrations in the coastal zone. Dissolved silicates and nitrate increase by over 10-fold in the acute phase. One year after the disaster the dissolved nutrients had increased at least 4-fold. Nitrogen enrichment leads to phosphorus and silica limitation in the coastal zone.